Two new species of Garra (Cypriniformes: Cyprinidae) from the lower Yarlung Tsangpo River drainage in southeastern Tibet, China - Gong, Zheng; Freyhof, Jörg; Wang, Jian; Liu, Meng; Liu, Fei; Lin, Pengcheng; Jiang, Yueliang; Liu, Huanzhang (Zootaxa, 2018)
Two new species of the fish genus Garra (Cypriniformes: Cyprinidae) are described from the lower Yarlung Tsangpo River drainage in southeastern Tibet, China. Garra motuoensis, a member of the proboscis species group, is primarily distinguished from the members of this group by having a prominent, quadrate, and slightly bilobed proboscis; 6–20 small to middle-sized unicuspid tubercles on the anterior region of the proboscis, some middle-sized unicuspid tubercles on the transverse lobe of the snout, and several small unicuspid tubercles on the lateral surface of snout; the anus situated slightly closer to the anal-fin origin than to the pelvic-fin origin (distance from anus to anal fin 36–46% of pelvic-anal distance); 36–37 lateral-line scales; and 12 circumpeduncular scales. Garra yajiangensis, a member of the proboscis species group, is primarily distinguished from the members of this group by having a prominent, quadrate, and slightly bilobed proboscis, covered with 2–7 middle-sized unicuspid tubercles, including two large-sized tubercles on anterior margin of each lobe; some small unicuspid tubercles on the transverse lobe and the lateral surface of snout; the anus situated substantially closer to the anal-fin origin than to the pelvic-fin origin (distance from anus to anal fin 19–24% of pelvic-anal distance); 34–36 lateral-line scales; and 12 circumpeduncular scales. The validities of these two new species were also corroborated by molecular phylogenetic analysis based on Cyt b gene sequences.